Dietary supplementation with rutin has pro-/anti-inflammatory effects in the liver of juvenile GIFT tilapia, Oreochromis niloticus. Issue 64 (May 2017) - Zheng, Yao; Zhao, Zhixiang; Fan, Limin; Meng, Shunlong; Song, Chao; Qiu, Liping; Xu, Pao; Chen, Jiazhang
Abstract: Dietary supplementation with rutin may have some pharmacological qualities including anti-inflammatory effects. Kupffer cell activation resulted in increased transcription of pro- and anti-inflammatory cytokines. The main purpose of this study was to investigate the pro- and anti-inflammatory activities in juvenile freshwater tilapia, Oreochromis niloticus, in response to 0.1 or 0.3 g/kg dietary supplementation of rutin. Results showed that hepatic IgM, anti-inflammatory-cytokines, and pro-inflammatory cytokines were significantly decreased in groups treated with high doses of rutin. Hepatic IgM and anti-inflammatory cytokines (IL-10 and IFN-γ) transcripts were significantly decreased, whereas the transcripts of the pro-inflammatory cytokines, TNFα and IL- 1 β were significantly decreased, whereas IL- 8 was significantly increased. The number of Kupffer cells in rutin-treated groups was significantly decreased, and scanning electron micrographs showed that rutin enriched the number of gut microvilli and secretion pits. With the phenomena of cell apoptosis occurred in the rutin groups, the present study demonstrated that optimum levels of rutin may be beneficial but excessive level may cause liver impairment, which may be absorbed by the gut and then transported to the liver. Highlights: Hepatic IgM, anti-inflammatory and pro-inflammatory cytokines significantly decreased. Hepatic IgM, IL- 10, IFN-γ, TNFα and IL- 1 β significantly decreased, whereas IL- 8 increased. The number of Kupffer cells significantly decreased. Rutin enriched the number of gut microvilli and secretion pits.